Performance modelling and analysis for vehicle‐to‐anything connectivity in representative high‐interference channels. Issue 13 (30th September 2019) - Blazek, Thomas; Ghiaasi, Golsa; Backfrieder, Christian; Ostermayer, Gerald; Mecklenbräuker, Christoph F.
Abstract : All too often, the performance of vehicular communications is benchmarked merely for a single link. A major challenge for benchmarking the performance of multiple interacting vehicles is the definition of repeatable vehicular scenarios. In this study, the authors propose and discuss an approach for performance analysis of the IEEE 802.11p standard in urban interference channels, by linking network simulations to a Software Defined Radio (SDR) setup. This approach provides communication performance measurements in the worst‐case interference scenario caused by an urban traffic jam. They do this by starting out with vehicular traffic flow simulations and continue to model the medium access. They furthermore introduce an algorithm to reduce the complexity of the communication network while retaining its properties. Finally, they use a setup of SDR encompassing the communication nodes and channel emulators that emulate urban channels to measure the packet level performance as a function of signal‐to‐interference ratio and distance to a receiver under urban traffic conditions.